Efficiency, Credit Risk and Financial Stability In National Banking Sector In Indonesia - Aliffianti Safiria Ayu Ditta; Rollis Ayu Ditasari; Arum Ardianingsih (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
Financial system stability in the banking system is crucial to be maintained so that there is no economic crisis that affects the stability of the country as a whole. The central role of banks as financial intermediaries makes banks have inherent risks, one of which is credit risk. Strict banking regulation aims to mitigate risks that can interfere with the main activities of banks both funding and lending activities. The relatively good level of national banking efficiency, greatly helps the banking sector to maintain financial system stability a midst of the high credit risks faced. The level of banking efficiency is a measure of how banks manage their resources so as to maintain their financial stability despite the fluctuating economic conditions.